Resilience and Work Engagement Among Employees in Multinational Companies: A Phenomenological Study - Elza Kusumawati; Rr. Amanda Pasca Rini; Salsabila Ratu Kencana Syaharani (Universitas Negeri Surabaya, 2026)
Background: The work environment becomes more complex due to globalization and cross-cultural performance demands. A multinational manufacturing company in East Java faces significant challenges in sustaining employee work engagement. Objective: This study aims to understand how employees in a multinational company experience and construe resilience in sustaining their work engagement. The research adopts Coulson’s (2006) resilience framework. Method: This qualitative study employed an Interpretative Phenomenological Analysis (IPA), involving 4 participants. Data were analyzed using IPA, with credibility ensured through triangulation, member checking, and peer debriefing. Results: Employees’ resilience in sustaining work engagement within a multinational company context is dynamic, from yielding to thriving. Engagement is initially minimal due to emotional strain, becomes more stable during recovery, and ultimately strengthens when work-related pressure is reinterpreted as a catalyst for continuous growth. Conclusion: Employee resilience is a dynamic and gradual process that shapes the sustainability of work engagement through adaptation to global pressures. This study highlights resilience as a regulatory mechanism and recommends emotional regulation training, coaching interventions, and the development of organizational psychological safety. Abstrak Latar Belakang: Lingkungan kerja semakin kompleks akibat globalisasi, teknologi, restrukturisasi, dan tuntutan kinerja lintas budaya. Perusahaan manufaktur multinasional di Jawa Timur menghadapi tantangan menjaga keterlibatan kerja karyawan akibat tekanan global, restrukturisasi, dan tuntutan kinerja. Tujuan: Penelitian ini bertujuan untuk memahami bagaimana karyawan di perusahaan multinasional mengalami dan memaknai resiliensi dalam mempertahankan keterlibatan kerja mereka. Penelitian ini mengadopsi teori resiliensi Coulson (2006). Metode: Penelitian kualitatif dengan pendekatan Interpretative Phenomenological Analysis (IPA) melibatkan 4 partisipan yang dipilih melalui purposive sampling. Analisis menggunakan IPA keabsahan melalui triangulasi, member checking, dan diskusi sejawat Hasil: Resiliensi karyawan dalam work engagement di perusahaan multinasional bersifat dinamis dan bertahap, dari mengalah hingga berkembang pesat. Keterlibatan awalnya minimal akibat tekanan emosional, kemudian stabil saat pemulihan, dan akhirnya kuat ketika tekanan dimaknai sebagai tantangan pertumbuhan berkelanjutan. Kesimpulan: Resiliensi karyawan bersifat dinamis dan bertahap, membentuk keberlanjutan work engagement melalui adaptasi terhadap tekanan global. Studi ini menegaskan peran resiliensi sebagai mekanisme regulatif, serta merekomendasikan pelatihan emosi, coaching, dan psychological safety organisasi.